2018
DOI: 10.1111/ggr.12216
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Potential of Nanoscale Re‐Os Isotope Systematics Using Atom Probe Microscopy

Abstract: Atom probe microscopy (APM) is a relatively new in situ tool for measuring isotope fractions from nanoscale volumes (< 0.01 μm3). We calculate the theoretical detectable difference of an isotope ratio measurement result from APM using counting statistics of a hypothetical data set to be ± 4δ or 0.4% (2s). However, challenges associated with APM measurements (e.g., peak ranging, hydride formation and isobaric interferences), result in larger uncertainties if not properly accounted for. We evaluate these factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 70 publications
(166 reference statements)
0
15
0
Order By: Relevance
“…Several recent studies have compared APT compositional results from geological samples with those from other geoanalytical techniques (Pérez‐Huerta et al , Daly et al , Exertier et al , Reinhard et al , Saxey et al ). Most comparisons provide excellent agreement, within the uncertainty arising from counting statistics in the atom probe data.…”
Section: Performance and Optimisationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have compared APT compositional results from geological samples with those from other geoanalytical techniques (Pérez‐Huerta et al , Daly et al , Exertier et al , Reinhard et al , Saxey et al ). Most comparisons provide excellent agreement, within the uncertainty arising from counting statistics in the atom probe data.…”
Section: Performance and Optimisationsmentioning
confidence: 99%
“…The atom probe provides a unique tool for investigating the nanoscale isotopic composition of minerals. Benchmarking of atom probe analysis of U isotopes in certified U 3 O 8 reference materials has shown that major isotopic ratios agree with known compositional values (Fahey et al ) and there are comparative thermal ion mass spectrometry (TIMS) and atom probe studies that show that Re‐Os analysis by atom probe may yield similar, though less precise, ages to more traditional TIMS analyses (Daly et al ). A number of studies have also investigated the mechanisms that can affect the distribution of radiogenic 207 Pb/ 206 Pb ratios in zircon (Figure ; Valley et al , , Peterman et al , Blum et al ), baddeleyite (White et al , Moser et al ) and monazite (Fougerouse et al , Seydoux‐Guillaume et al ).…”
Section: Geoscience Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of APM to radiogenic isotope geochemistry has been demonstrated using the U-Pb system [8 10]. And other radiogenic systems, such as Sm-Nd and Re-Os, also appear amenable to the technique, where concentrations permit [72]. Within this field, the atom probe is an ideal tool for determining the origin and history of geological materials from sub-micron isotopic signatures, which are often not resolvable using other techniques.…”
Section: Isotopic Analysis: Tracers and Chronometersmentioning
confidence: 99%
“… Daly et al (2017b) performed APM analyses of sub-micrometer PGE-rich refractory metal nuggets contained within a Sc-Zr–rich ultrarefractory inclusion from the ALH 77307 CO3.0 meteorite. More recently, Daly et al (2018) employed the laser-assisted APM technique to measure Re and Os isotope ratios of pure Os, pure Re, and synthetic Re-Os-bearing alloys, demonstrating that the APM technique permits nanoscale Os isotope ratio measurements of Os-bearing alloys to yield similar, though less precise, ages to NTIMS analyses. At current, development and application of the analytically expensive and highly-specific APM technique in geosciences is still in its early stages ( Reddy et al, 2020 ).…”
Section: In-situ Techniques For Os Isotope Ratio and Re Pgementioning
confidence: 99%